A2Bn-1PbnI3n+1 (A = BA, PEA; B = MA; n = 1, 2): engineering quantum-well crystals for high mass density and fast scintillators - Md Abdul Kuddus Sheikh (2024)
Quantum-well (QW) hybrid organic-inorganic perovskite (HOIP) crystals, e.g., A2PbX4 (A = BA, PEA; X = Br, I), demonstrated significant potentials as scintillating materials for wide energy radiation detection compared to their individual three-dimensional (3D) counterparts, e.g., BPbX3 (B = MA). Inserting 3D into QW structures resulted in new structures, namely A2BPb2X7 perovskite crystals, and they may have promising optical and scintillation properties toward higher mass density and fast timing scintillators. In this article, we investigate the crystal structure as well as optical and scintillation properties of iodide-based QW HOIP crystals, A2PbI4 and A2MAPb2I7. A2PbI4 crystals exhibit green and red emission with the fastest PL decay time <1 ns, while A2MAPb2I7 crystals exhibit a high mass density of >3.0 g/cm3 and tunable smaller bandgaps <2.1 eV resulting from quantum and dielectric confinement. We observe that A2PbI4 and PEA2MAPb2I7 show emission under X- and γ-ray excitations. We further observe that some QW HOIP iodide scintillators exhibit shorter radiation absorption lengths (∼3 cm at 511 keV) and faster scintillation decay time components (∼0.5 ns) compared to those of QW HOIP bromide scintillators. Finally, we investigate the light yields of iodide-based QW HOIP crystals at 10 K (∼10 photons/keV), while at room temperature they still show pulse height spectra with light yields between 1 and 2 photons/keV, which is still >5 times lower than those for bromides. The lower light yields can be the drawbacks of iodide-based QW HOIP scintillators, but the promising high mass density and decay time results of our study can provide the right pathway for further improvements toward fast-timing applications.